Beyond tradition contemporary Indian art and its evolution (Pheonix, Ariz Jacka Photography, 1989)
Presents more than three hundred examples of prehistoric, historic and contemporary American Indian art.
VHS format.
Jerry Jacka, photographer, and leading Native American artists.
Keywords: Indian art; Indian art -- North America; Art, American -- 20th century